P68 Adolescent drinking in Chile: Does it matter which school they go to?. (13th September 2016) - Roman Mella, MF; Cable, N; Kelly, Y; Nicholas, O
Abstract : Background: Parents and peers play a significant role in adolescent drinking, however less is known about the influence of school socioeconomic environment on alcohol use. Chile is an example of how socioeconomic segregation can cast a shadow on the quality of state-funded education, causing a social gap in adolescents' academic achievement. Studying adolescent drinking in Chile where the schooling system is socially segregated could offer insights into how such behaviour could be reduced. This study aims to examine associations between school socioeconomic environment and adolescent drinking patterns, taking into account individual and parental factors. Methods: Multilevel analyses were conducted on cross-sectional data with three-level nested structure: pupils within classes within schools. Individual-level information was extracted from a nationally representative survey (N = 58, 148, aged 13 to 18) conducted in 2013 (School Population National Substance Use Survey) and linked to school-level data (N = 1, 687). Patterns of non-drinking (having never drunk), non-binge drinking (having drunk but not bingeing) and binge drinking (consumption of five or more drinks in the past month) were identified at the individual level. At the school level, schools were classified into five socioeconomic groups (low, lower middle, middle, upper middle and high) using an official classification provided by the Ministry of Education. Multilevel logistic regression models of non-binge drinking (vs. non-drinking) and binge drinking (vs. non-binge drinking) were stratified by gender and adjusted for individual-level variables: child's age, father's and mother's education, parental knowledge of whereabouts and father's and mother's drinking. Analyses were performed using MLwiN 2.35 from within STATA 13. Results: About half the participants reported having consumed alcohol but not having engaged in binge drinking [51.6%; 95% CI 50.7, 52.5]. Thirty percent of participants reported binge drinking in the past month [30.4%; 95% CI 29.5, 31.3]. The proportion of binge drinkers was larger in boys than girls and in pupils attending socially disadvantaged schools. Results obtained from multilevel analyses suggested that pupils attending socially disadvantaged schools had decreased odds of non-binge drinking compared to those attending advantaged schools (ORboys = 0.46, 95% CI 0.39–0.55; ORgirls = 0.73, 95% CI 0.60–0.88). Conversely, pupils attending disadvantaged schools were more likely to engage in binge drinking than those attending advantaged schools (ORboys = 1.24, 95% CI 1.07–1.42; ORgirls = 1.75, 95% CI 1.51–2.03). Conclusion: Results suggest that adolescents attending socially disadvantaged schools may be at higher risk of binge drinking and its negative consequences. This may contribute to the accumulation of harm related to alcohol use within disadvantaged groups.